2017
DOI: 10.1371/journal.pone.0188155
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of the Atypical Hemolytic Uremic Syndrome after kidney transplantation treated with eculizumab as first choice

Abstract: IntroductionThe treatment of choice for Atypical Hemolytic Uremic Syndrome (aHUS) is the monoclonal antibody eculizumab. The objective of this study was to assess the efficacy and safety of eculizumab in a cohort of kidney transplant patients suffering from aHUS.MethodsDescription of the prospective cohort of all the patients primarily treated with eculizumab after transplantation and divided into the therapeutic (onset of aHUS after transplantation) and prophylactic use (patients with previous diagnosis of aH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Graft survival after de novo TMA was 43% in 4 years, significantly less than those who did not have TMA after kidney transplant (85.6%) (18). The early CNI withdrawal in de novo TMA patients probably decreased biopsies indications after kidney transplant in our hospital, which performs on average 120 kidney transplants a year (19).…”
Section: Discussionmentioning
confidence: 72%
“…Graft survival after de novo TMA was 43% in 4 years, significantly less than those who did not have TMA after kidney transplant (85.6%) (18). The early CNI withdrawal in de novo TMA patients probably decreased biopsies indications after kidney transplant in our hospital, which performs on average 120 kidney transplants a year (19).…”
Section: Discussionmentioning
confidence: 72%
“…Fifteen real-life NRSI including individuals with PNH ( n = 4189) and aHUS ( n = 1090) were assessed mathematically into pairwise level. As observed in Figure 4 , a protective effect from eculizumab was evident in hemolysis in PNH [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], TMA in aHUS [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ], and AKI in aHUS [ 53 , 54 , 55 , 56 , 57 , 58 , …”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, clinical trials and real-life NRSI did not assess adult and pediatric populations separately [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , ...…”
Section: Resultsmentioning
confidence: 99%
“…An additional three articles were excluded because they were case reports or single cases treated with eculizumab [8,38,39]. Ultimately 18 studies (13 cohort studies and five case series) [5,9,15,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54] consisting of 380 patients with a history of aHUS who received eculizumab for prevention and treatment of post-transplant recurrent aHUS were included into the final analysis. The literature review and selection process are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%